Occupational Transmission of Measles Despite COVID-19 Precautions - Gabriella De Carli; Emanuela Giombini; Alberto Colosi; Maria Concetta Fusco; Eleonora Lalle; Giulia Berno; Martina Rueca; Lavinia Fabeni; Licia Bordi; Fabrizio Maggi; Maurizio D’Amato; Valentina Vantaggio; et al. (Pathogens)
To determine whether patient-to-doctor transmission of measles occurred in an emergency department (ED) despite isolation precautions and full personal protective equipment (PPE) during the COVID-19 pandemic, an epidemiological and molecular investigation was carried out following the identification of two subsequent cases. The N fragment was used to identify the closest whole measles genome present in the GenBank nr database and, subsequently, this was used as a reference for the reconstruction of the entire MeV sequence in the two cases studied. Seven measles-susceptible healthcare workers were on duty the day of admission of the patient, wearing full PPE. The infected doctor neither visited the patient nor entered the isolation room. The patient wore a facial respirator. No breaches in infection control procedures, or other cases among contacts, patients and healthcare workers were identified. Molecular analysis provided evidence of patient-to-worker transmission: the two B3 genome sequences showed only one mutation and no sequences of other countries were identified as phylogenetically related. Isolation precautions and full PPE were widely implemented in the ED during the COVID-19 pandemic; however, this did not prevent nosocomial transmission of measles. Vaccination of healthcare workers and enhanced ventilation should complement other preventive measures to protect workers and patients.